Memberdayakan UMKM Berbasis Komunitas melalui Konten Digital Inklusif: Program Pelatihan Kreatif untuk Social Media Engagement - Kurniawan Prasetyo; Siti Muslichatul Mahmudah; Rio Meilandri (Yayasan Literasi Sains Indonesia, 2025)
This community service program was initiated in response to the limited capacity of community-based MSMEs in utilizing inclusive digital content to improve their marketing performance and customer engagement. Many MSMEs struggle with creating visually appealing and accessible content due to a lack of technical skills, strategic planning, and understanding of digital branding. The goal of this activity was to empower MSMEs and vocational school students in South Tangerang by enhancing their ability to create inclusive, creative, and impactful social media content. The program applied a participatory empowerment approach, combining training, mentoring, and hands-on workshops. The results showed a significant improvement in the participants’ skills in content creation, digital branding, and audience engagement strategies. Participants also demonstrated behavioral changes, such as consistent posting schedules and increased use of storytelling formats. The activity received wide community appreciation and was featured in multiple online media, indicating strong public relevance. It also aligned with several Sustainable Development Goals (SDGs), particularly in quality education, economic growth, and innovation. In conclusion, the service program effectively contributed to building digital competence and inclusive communication practices among MSMEs. Future initiatives are encouraged to adopt adaptable, inclusive, and community-oriented approaches to maximize impact and sustainability.